How is high quality research evidence used in everyday decisions about induction of labour between pregnant women and maternity care professionals? An exploratory study. (September 2021) - Farnworth, Allison; Graham, Ruth H; Haighton, Catherine A; Robson, Stephen C
Abstract: Objective: To explore the use of high quality research evidence in women's and maternity care professionals' decisions about induction of labour (IOL). Methods: A qualitative study underpinned by a social constructionist framework, using semi-structured interviews and generative thematic analysis. Setting: A large tertiary referral maternity unit in northern England in 2013/14. Participants: 22 randomly selected health care professionals involved in maternity care (midwives, obstetricians, maternity service managers), and 16 postnatal women, 3-8 weeks post-delivery, who were offered IOL in their most recent pregnancy. Findings: Three themes were identified in the data; (1) the value of different forms of knowledge, (2) accessing and sharing knowledge, and (3) constrained pathways and default choices. Findings echo other evidence in suggesting that women do not feel informed about IOL or that they have choices about the procedure. This study illuminates potential explanatory factors by considering the complex context within which IOL is discussed and offered (e.g. presentation of IOL as routine rather than a choice, care pathways that make declining IOL appear undesirable, blanket use of clinical guidelines without consideration of individual circumstances and preferences). Key conclusions: This study suggests that organisational, social, and professional factors conspire towards a culture where (a) IOL has become understood as a routine part of maternity care rather than an intervention to make an informed choice about, (b) several factors contribute to demotivate women and health care practitioners from seeking to understand the evidence base regarding induction, and (c) health care professionals can find themselves ill-equipped to discuss the relative risks and benefits of IOL and its alternatives. Implications for practice: It is important that IOL is recognised as an optional intervention and is not presented to women as a routine part of maternity care. When IOL is offered it should be accompanied by an evidence informed discussion about the options available to support informed decision making. Health care professionals should be supported to understand the evidence base and our findings suggest that any attempt to facilitate this needs to acknowledge and tackle complex organisational, social and professional influences that contribute to current care practices.